2007
DOI: 10.1124/jpet.106.112649
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Approaches Identify Differential Roles for α4β2*Nicotinic Receptors in Acute Models of Antinociception in Mice

Abstract: The effects of nicotine on the tail-flick and hot-plate tests were determined to identify nicotinic receptor subtypes responsible for spinally and supraspinally mediated nicotine analgesia in knockin mice expressing hypersensitive ␣ 4 nicotinic receptors (L9ЈS), in seven inbred mouse strains (C57BL/6, DBA/2, A/2, CBA/2, BALB/ cByJ, C3H/HeJ, and 129/SvEv), and in two F1 hybrids (B6CBAF1 and B6D2F1). L9ЈS heterozygotes were ϳ6-fold more sensitive to the antinociceptive effects of nicotine than the wild-type cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 30 publications
3
46
0
1
Order By: Relevance
“…WT, ␣4YFP, and ␣4 KO (Ross et al, 2000) mice showed similar baseline reaction times to sensing pain on the hot plate. Similar to the previous studies (Marubio et al, 1999;Damaj et al, 2007), we found that ␣4 KO mice (Ross et al, 2000) are relatively resistant to nicotine-induced antinociception, whereas ␣4YFP Hom, Het, and WT mice showed similar pharmacological sensitivity to nicotine-induced antinociception (supplemental Fig. S3, available at www.jneurosci.org as supplemental material).…”
Section: Characterizing the ␣4yfp Mice: Normal Nicotinic Receptor Funsupporting
confidence: 75%
See 1 more Smart Citation
“…WT, ␣4YFP, and ␣4 KO (Ross et al, 2000) mice showed similar baseline reaction times to sensing pain on the hot plate. Similar to the previous studies (Marubio et al, 1999;Damaj et al, 2007), we found that ␣4 KO mice (Ross et al, 2000) are relatively resistant to nicotine-induced antinociception, whereas ␣4YFP Hom, Het, and WT mice showed similar pharmacological sensitivity to nicotine-induced antinociception (supplemental Fig. S3, available at www.jneurosci.org as supplemental material).…”
Section: Characterizing the ␣4yfp Mice: Normal Nicotinic Receptor Funsupporting
confidence: 75%
“…Previous work showed that ␣4* nAChRs mediate nicotineinduced antinociception on the hot plate (Marubio et al, 1999;Damaj et al, 2007). WT, ␣4YFP, and ␣4 KO (Ross et al, 2000) mice showed similar baseline reaction times to sensing pain on the hot plate.…”
Section: Characterizing the ␣4yfp Mice: Normal Nicotinic Receptor Funmentioning
confidence: 99%
“…These data suggest that C57BL/6 mice have increased sensitivity to the rewarding properties of nicotine relative to other strains. Inbred mouse strains such as A/J and 129/SvEv mice were more sensitive to the antinociceptive effects of acute nicotine than C57BL/6J and DBA/2Ibg mice [29]. However, C57BL/6J mice showed increased sensitivity to pain during nicotine-precipitated withdrawal, but precipitated withdrawal had no effect on pain perception in 129/SvEv mice [28].…”
Section: The Effects Of Nicotine In Inbred Rodent Strainsmentioning
confidence: 97%
“…The mutation is lethal to homozygous mice but not to heterozygous mice that possess a neomycin resistance cassette [86]. Subsequent research has demonstrated that Leu9'Ser heterozygous mice are more sensitive to the antinociceptive effects of nicotine than WT mice [29]. Although in vivo research using Leu9'Ser mice is limited to heterozygotes, Tapper and colleagues [167] have shown that Leu9'Ala homozygous mice are viable and will exhibit a ~50-fold increase in sensitivity to nicotine, develop nicotine CPP at a ~50-fold lower dose of nicotine than in WT mice, and develop tolerance to nicotine-induced changes in body temperature at a ~50-fold lower dose of nicotine.…”
Section: The α4 Nachr Subunitmentioning
confidence: 99%
“…This approach may be a useful way to inducibly destroy midbrain DA neurons similar to the DA neuron loss seen in Parkinson's disease (Schwarz et al, 2006). ␣4 L9ЈS mice also highlight the importance of ␣4* nAChRs in analgesic pathways and mechanisms, because ␣4 L9ЈS heterozygotes were 6-fold more sensitive to the antinociceptive effect of nicotine in the hotplate assay (Damaj et al, 2007). …”
mentioning
confidence: 99%